Selecting authentic audiovisual materials and designing authentic tasks in the AFL classroom: Criteria and challenges - Hamed, Mohamed Hassan (AUC Knowledge Fountain, 2017)
This study investigated the criteria of selecting authentic audiovisual materials (AAM) and designing authentic tasks (AT) as well as the challenges which teachers of Arabic as a Foreign Language (AFL) encounter when selecting AAM and designing AT in the AFL classroom. Data collection procedures included an online questionnaire, classroom observations, and teachers’ interviews. Data collection followed this order: 112 respondents from various teaching backgrounds were surveyed, five AFL classrooms were observed, and four AFL instructors in a private university in Egypt were interviewed. Data was quantitatively and qualitatively analyzed. The results indicated that AFL teachers frequently use news, songs, and movies. The AFL teachers illustrated that AAM could be used at all levels, and they mainly use them to raise cultural awareness. Furthermore, results demonstrated that AFL teachers commonly follow specific criteria when selecting AAM and designing AT. Moreover, results illustrated that AFL teachers face challenges when selecting AAM and when designing AT. The task of finding AAM is difficult in terms of conducting the search, making a selection, and screening the vocabulary. On the other hand, the main challenges when designing AT include: effort, time, need for training, and preparation of appropriate activities to accurately measure learners’ levels. The results revealed that AFL teachers need training to select the suitable AAM for each level, to prepare an AAM-based curriculum, and to use technological tools. The results also demonstrated that AFL teachers lack a clear understanding of AT, which implies focusing on developing AFL teachers’ skills to effectively prepare AT. Such results, therefore, support the hypothesis that AFL teachers lack a clear understanding of AT. In response, certain pedagogical implications are proposed.